Extrinsic and intrinsic factors in the Balanced Scorecard adoption: An empirical study in Portuguese organizations - Patrícia Rodrigues Quesado; Beatriz Aibar-Guzmán; Lúcia Lima Rodrigues (European Journal of Management and Business Economics (EJM&BE), 2016)
In this article we aim to analyze the relationship between a set of organizational extrinsic and intrinsic factors and the adoption of the Balanced Scorecard (BSC) by privately-owned Portuguese organizations (large companies and small and medium enterprises). These factors are related to companies age, the diversity of products and services, the nature of the ownership structure, the internationalization, and the organizational size. As a primary means of data collection was carried out a postal survey through a questionnaire sent to 549 privately-owned Portuguese organizations, with an overall response rate of 28.2%. The results indicate that the degree of diversity of the products/services of the organization, the ownership of foreign groups, and the organizational size are positively associated with the implementation of the BSC. Thus, we conclude that the BSC increases with the degree of diversity of the products/services of the organization, that the Portuguese organizations that use the BSC are mainly owned by foreign groups; and larger organizations are most likely to use this tool.
Keywords: M10; M41; 650; Balanced Scorecard; Contingency Theory; Determining factors; Environmental factors; Organizational factors; Portuguese firms